Instability of Self-Assembled Monolayers (SAM) as a Model Material System for Macrophage/FBGC Cellular Behavior - Jones, Jacqueline A. (2008)
Novel self-assembled monolayers (SAMs) designed to present homogenous surface chemistries were utilized to further investigate the material surface chemistry dependent macrophage and foreign body giant cell (FBGC) behaviors including macrophage adhesion, fusion, and apoptosis. Contact angle analysis revealed instabilities in the –CH(3) and –COOH terminate SAM surfaces upon incubation in serum-free media at 37(o)C or under dry, room temperatureconditions. Further analysis indicated that the –CH(3) terminated SAM surface degraded rapidly within 2 hours and loss of sufficient SAM units to be comparable to the gold (Au) control surface within 24 hours of incubation in serum-free media (SFM) at 37(o)C. After 5days of incubation in SFM at 37(o)C, the contact angles for the –COOH terminated SAMsurfaces increased markedly. AFM analysis confirmed the desorption of –CH(3) terminated SAM molecules from the surface with increased roughness and marked appearance of peaks andvalleys within 2 hours. A decrease in the thickness of the –COOH terminated SAM surface also suggests molecular desorption over time. No significant changes in contact angle or AFM analyses were observed on the –OH terminated SAM surfaces. Cellular adhesion decreased morerapidly on the Au control and –CH(3) terminated SAM surfaces in comparison to the other surfaces. However by day 10, cellular adhesion, fusion, and apoptosis were comparable on all SAM surfaces and the Au control . These studies suggest that SAM surfaces may not be suitable for long-term studies where material dependent properties are investigated.